Diaquaiodido(2,3,5,6-tetra-2-pyridylpyrazine-κ3N2,N1,N6)manganese(II) iodide monohydrate - Kwang Ha (Acta Crystallographica Section E, 2011)
The asymmetric unit of the title compound, [MnI(C24H16N6)(H2O)2]I·H2O, consists of a cationic MnII complex, an I− anion and a solvent water molecule. In the complex, the MnII ion is six-coordinated in a considerably distorted octahedral environment defined by three N atoms of the tridentate 2,3,5,6-tetra-2-pyridylpyrazine (tppz) ligand, one I− anion and two O atoms of two water ligands. The dihedral angles between the pyridyl rings [maximum deviation = 0.034 (6) Å] and their carrier pyrazine ring [maximum deviation = 0.020 (6) Å] are 26.5 (2) and 27.0 (2)° for the coordinated pyridyl rings, and 51.3 (3) and 43.2 (2)° for the uncoordinated pyridyl rings. Intermolecular O—H...O, O—H...N and O—H...I hydrogen bonds stabilize the crystal structure.